2017
DOI: 10.1002/jcp.25888
|View full text |Cite
|
Sign up to set email alerts
|

2‐methoxyestradiol impacts on amino acids‐mediated metabolic reprogramming in osteosarcoma cells by its interaction with NMDA receptor

Abstract: Deregulation of serine and glycine metabolism, have been identified to function as metabolic regulators in supporting tumor cell growth. The role of serine and glycine in regulation of cancer cell proliferation is complicated, dependent on concentrations of amino acids and tissue-specific. D-serine and glycine are coagonists of N-methyl-D-aspartate (NMDA) receptor subunit GRIN1. Importantly, NMDA receptors are widely expressed in cancer cells and play an important role in regulation of cell death, proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…Importantly, the pro-migratory and proproliferative effects of L-lactate were reversed by treatment with a pharmacological concentration of 2-ME. The antimigratory potential of 2-ME has previously been demonstrated in various experimental models (17,23,24). Herein, for the first time, we demonstrated the antagonistic effect between 2-ME and L-lactate.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Importantly, the pro-migratory and proproliferative effects of L-lactate were reversed by treatment with a pharmacological concentration of 2-ME. The antimigratory potential of 2-ME has previously been demonstrated in various experimental models (17,23,24). Herein, for the first time, we demonstrated the antagonistic effect between 2-ME and L-lactate.…”
Section: Discussionsupporting
confidence: 58%
“…An anticancer mechanism of 2-ME is associated with the induction of mitochondrial oxidative stress resulting in the induction of the mitochondrial apoptotic pathway in cancer cells (38,42). It was previously demonstrated that 2-ME decreased mitochondrial membrane potential due to generation of nitro-oxidative stress leading to cancer cell death (17)(18)(19)(20)(21)43). However, 2-ME also works as an inhibitor of mitochondrial respiration by inhibiting Complex I (39-41).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we evidenced that generation of NO due to nuclear recruitment of nNOS constitutes an anticancer mechanism of 2-methoxyestradiol (2-ME) action ( Figure 1) (18). 2-ME is a natural derivative of 17β-estradiol that possesses anticancer activities, as confirmed by in vitro and in vivo studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Under the brand name Panzem, 2-ME is being evaluated in clinical trials for the treatment of numerous malignancies, such as breast and prostate cancers (19)(20)(21)(22).…”
mentioning
confidence: 80%
“…The membranes were then incubated with primary antibodies specific to α-syntrophin or PGC-1α (1:2000) overnight at 4˚C, or β-Actin (1:50000) for 30 min at room temperature. Analysis was performed as previously described (26). Chemiluminescence was detected using ImageQuant LAS 500 (GE Healthcare, Warsaw, Poland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation